THE ORGANIZATION OF COMPARATIVE STUDIES - Чальцева, О.М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
In the article the process of organizing the comparative studies is analyzed. The stages of comparative analysis are isolated. Basic difficulties with the isolation of the object field of of the Comparative Politics and about classification of comparative studies with diffirent aspects are examined.